Customer relationship management a global approach - Chakravorti, Samit (SAGE, 2023)
Customer Relationship Management: A Global Approach provides a uniquely global, holistic, strategic and tactical grounding in managing customer and other stakeholder experiences and relationships across the value chain, cultures and countries. Reflecting the global structures of companies operating today, the author draws on his research knowledge alongside industry and teaching experience to connect Customer Relationship Management (CRM) core concepts, processes and strategies with international business opportunities and challenges, including globalization and cross-cultural marketing. Emphasis is placed on the need for developing cross-cultural skills and cultural intelligence for identifying and fulfilling cross country CRM opportunities, through analytical, strategic, operational and social CRM projects. Written in an accessible style throughout, the eleven chapters provide ample depth to support a full course related to CRM, spanning: CRM foundations planning and implementation managing stakeholder relationships improving global CRM implementation Wide-ranging case studies include: Royal Bank of Scotland, the Nike hijab, Instagram, HubSpot and the pharmaceutical industry in India. The text will appeal to advanced undergraduate and graduate students studying CRM, Relationship Marketing and International Marketing, as well as CRM and marketing practitioners. Samit Chakravorti is an Associate Professor of Marketing at Western Illinois University in the United States"--